Phenomenological-contextual approach to study freedom in psychology - Prusiński, Tomasz (Studia Psychologica: Theoria et praxis, 2011)
Freedom as a subject of academic research in psychology has always been confined to a space regarded as difficult to explore. Since the beginning of psychology as a branch of science, the discussion of freedom has been fragmented. The adoption of a specific repertoire of methodological and philosophical assumptions has ignited interest in the topic and issues of freedom. The history of freedom being present in psychology is an ongoing struggle between different paradigms regarding the nature of this subject and its associated methods of examination. During the nineties of the last century, there was a shaping of the direction referring to the achievements of humanistic psychology, as emphasizing the importance of subjective human experience. The authors of this approach, taking care of a methodological workshop and conducting a series of empirical studies, have proposed a new approach to the study of freedom in psychology. The most important achievement of the phenomenological-contextual approach was to draw attention to the possibility of exploring in scientific research the phenomenon of freedom in psychology that has been rejected as a matter of the intersection of science and philosophy.